The effect of BEAM Plus certification on property price in Hong Kong - Hui, Eddie C. M.; Tse, Cheuk-kin; Yu, Ka-hung (International Journal of Strategic Property Management, 2017)
In response to the public’s increasing awareness of sustainable development, the construction industry has introduced “green” buildings which emphasize better environmental performance. However, as a building’s environmental performance is difficult to discern for laymen, different green building certifications have been established for evaluations in this regard. This study evaluates whether there exists a price premium for living space in buildings certified with BEAM Plus. The findings show that the prices of flats in BEAM Plus-certified buildings are 4.4% higher than those in nonregistered buildings, and that housing units in buildings with an “unclassified” rating are transacted at a discount of 5.9%. Nevertheless, if homebuyers mistake an “unclassified” building for a non-registered building, due to the non-disclosure of the “unclassified” result by developers, the price premium of BEAM Plus certification becomes higher (6.2%). Regardless, the price premium is much lower than those on the office sector. The reasons behind such differences can be attributed to the disparities in the tangible and intangible benefits associated with green living space and green office space. Policy implications with reference to Hong Kong’s GFA concession policy are then discussed.